Fund financial management strategy effort to improve accountability and sustainability of village government leadership - Asdi; Nur Sitti Khumairoh; Muhamad Risal Tawil; Agustian Zen; Nenden Hendayani (Enrichment : Journal of Management, 2023)
This paper's research aimed to collect practical information concerning village financial management activities and methods for strengthening the accountability and sustainability of village government leadership. Several studies have been conducted to assess the efficacy and advantages of the Village Fund allocation budget. Only some studies, however, have looked at village financial management data management techniques that are responsible and sustainable for village government leadership. Methods for managing village money are adopted that adhere to the purposes and objectives of the village budget and improve the dignity of village-level leadership via efficient governance following existing legislation. Following the acquisition of various supporting documents, we evaluated them using a phenomenological technique, a tool we used to comprehend the phenomena of a Village-related problem. We can summarize the results, among others, that we get the function of village fund allocation intended for accelerating the development of village governance as well as an implementation strategy including accountability financial planning and a system of accountability for using these funds following the stages and policies determined by the central government and followed by adaptation to the interests of the local Village. Thus this study may be helpful for further studies.